Voice Onset Time in Azerbaijani Consonants - Ali Jahan (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: Voice onset time is known to be cue for the distinction between voiced and voiceless stops and it can be used to describe or categorize a range of developmental, neuromotor and linguistic disorders. The aim of this study is determination of standard values of voice onset time for Azerbaijani language (Tabriz dialect). Materials & Methods: In this description-analytical study, 30 Azeris persons whom were selected conveniently by simple selection, uttered 46 monosyllabic words initiating with 6 Azerbaijani stops twice. Using Praat software, the voice onset time values were analyzed by waveform and wideband spectrogram in milliseconds. Vowel effect, sex differences and the effect of place of articulation on VOT, were evaluated and data were analyzed by one-way ANOVA test. Results: There was no significant difference in voice onset time between male and female Azeris speakers (P<0.05). Vowel and place of articulation had significant correlation with voice onset time (P<0.001). Voice onset time values for /b/, /p/, /d/, /t/, /g/, /k/, and [c], [ɟ] allophones were 10.64, 86.88, 13.35, 87.09, 26.25, 100.62, 131.19, 63.18 mili second, respectively. Conclusion: Voice onset time values are the same for Azerbaijani men and women. However, like many other languages, back and high vowels and back place of articulation lengthen VOT. Also, voiceless stops are aspirated in this language and voiced stops have positive VOT values.